Meminimalisir kerusakan dalam penyimpanan produk hasil panen dengan memperhatikan kelembapan - Risgunawati, Amelya Tanjung (Maliki Interdisciplinary Journal, 2023)
Humidity can affect the quality of a product. The more humid a product is, the more water content is contained in the product. This can change the durability of a product. Not only crop products but all kinds of products can be affected by their quality and become damaged more quickly due to the influence of moisture. The wrong way to store products can also accelerate the damage of a product. For example, A product that should be stored in a dry condition but stored in a humid condition can spoil the product more quickly. When the product is stored in a dry state, the product can last longer, and the water content in the product when the product is dry is less than when the product is stored in a humid condition. Damage to a product, especially crop yields, can cause losses, both for the farmers themselves and for the traders. These losses can be minimized if we know and understand the causes and take prevention or anticipation to improve product quality.